29. THE CLINICAL CHARACTERISTICS AND ENDOSCOPIC FEATURES OF PATIENTS WITH GASTRODUODENITIS AND PEPTIC ULCERS AT HA DONG GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Objective: Gastroduodenitis and peptic ulcers are common digestive diseases, directly affecting thehealth and quality of life of patients. The study aimed to describe the clinical characteristics andendoscopic features of patients with gastroduodenitis and peptic ulcers at Ha Dong General Hospital.Subject and method: Cross-sectional descriptive study was conducted on 202 patients who camefor examination and treatment at Ha Dong General Hospital from October 2023 to April 2024.Results: Male/female ratio: 1/1.32. The average age: 51.06 ± 18.05, the youngest is 18 years old,the highest is 92 years old. The majority of subjects had a history of gastroduodenopathy (53.5%),11.9% of subjects had a history of cardiovascular and metabolic diseases (diabetes mellitus,hypertension). The most common symptom is upper abdominal pain with 94.1%. 78.2% of subjectshad endoscopy results of inflammatory lesions. 45% of subjects had positive HP results. Withinflammatory lesions, the main characteristics are edema and congestion (59.4%), and the positiveHP rate is 43%. With ulcer lesions, the positive HP rate was 38.1%, mainly subjects had 1 ulcer(65.9%), patients had at most 5 ulcers. Ulcers are mainly in the stomach (61.4%). 86.3% of thebase had pseudomembrane, the margin was mainly edematous (65.5%).Conclusion: Inflammatory lesions and peptic ulcers can occur in all subjects, but mostly in middleaged and older people, the recurrence rate is high, and the symptoms are diverse and non-specific.Inflammatory lesions are more common than ulcers, and the positive rate for HP is high.
Keywords: Gastroduodenitis and peptic ulcers, HP positive, endoscopic features.